Implementing an android-based Learning Media Application to Improve Learners' Ability in Pronouncing Ending-s - Fathira, Vina; Utami, Silvia (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2019)
This research was done based on the needs to improve the learners’ ability in pronunciation of ending –s by using android based application. Android based becomes popular in this era since gadget applies many applications to improve English language proficiency. The aim of the research is to implement the application on android based to improve the learners’ ability in pronouncing ending –s and to find the influencing factors of the improvement. The method of this research was qualitative. This Classroom Action Research was conducted at eight second-year-learners in academic year 2018/2019 at STIBA Persada Bunda Pekanbaru. There were tests, fieldnotes, observation, and interview used in the data collecting techniques in this research. The result shows that implementing the application existed on android based learning media to improve learners’ ability in pronouncing ending –s has significantly improved. It can be seen that the learners’ ability in pronouncing ending –s are at the “fairly good” level category with score 56,67 increases to the “good” level category with score 73,75. Some influential factors towards the learners’ improvement were affected by the students’ willingnes to practice  differentiating the base form of word given and continuous listening practice to the application which was aimed to obtain the information during the teaching-learning process. In conclusion, the implementation of application on android based can improve the learners’ ability in pronouncing ending –s.